2021
DOI: 10.1007/s40121-021-00407-9
|View full text |Cite
|
Sign up to set email alerts
|

The Seasonality of Peripheral Venous Catheter-Related Bloodstream Infections

Abstract: Introduction: Although the seasonality of infectious diseases has been widely reported, the seasonality of peripheral venous catheterrelated bloodstream infection (PV-CRBSI) has not been investigated. This study investigated the seasonality of PV-CRBSI and its relationship with meteorological conditions. Methods: A retrospective cohort study of PV-CRBSI at Tokyo Medical University Hospital (Tokyo, Japan), from 2009 to 2019, provided the data for descriptive and time series analyses used to evaluate the number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…The detection rate of B. cereus in blood culture-positive samples is 1.2% according to the information published from the Japan Nosocomial Infections Surveillance (JANIS) in 2020. The rates in A and B Hospitals (736 and 904 beds, respectively) were 1.7 and 22.2%, respectively 28 . It is highly probable that bed bath towels contaminated with B. cereus may have contributed to the high outbreak rates of B. cereus in B Hospitals measured in the blood-culture-positive samples.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The detection rate of B. cereus in blood culture-positive samples is 1.2% according to the information published from the Japan Nosocomial Infections Surveillance (JANIS) in 2020. The rates in A and B Hospitals (736 and 904 beds, respectively) were 1.7 and 22.2%, respectively 28 . It is highly probable that bed bath towels contaminated with B. cereus may have contributed to the high outbreak rates of B. cereus in B Hospitals measured in the blood-culture-positive samples.…”
Section: Discussionmentioning
confidence: 97%
“…However, an increasing number of studies suggested that B. cereus causes serious septicemia (bacteremia) [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. In addition, the administration of peripheral parenteral nutrition containing glucose, amino acids, and electrolytes (PPN) [22][23][24][25] and the summer season [26][27][28] have been indicated as risk factors for B. cereus-related septicemia. Of these risk factors, the former was extracted because B. cereus may proliferate in PPN.…”
Section: Introductionmentioning
confidence: 99%
“…2 CLABSI has been a significant challenge in care and has increased health care costs and mortality. [3][4][5] On the other hand, the prevalence of CVC-related infections in the ICU can lead to healthcare-acquired infections (HCAIs). HCAIs are infections that occur within 48 to 72 hours or more after hospitalization.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, central line‐associated bloodstream infections (CLABSI) are among the most lethal complications associated with CVC use in intensive care units (ICU) 2 . CLABSI has been a significant challenge in care and has increased health care costs and mortality 3–5 . On the other hand, the prevalence of CVC‐related infections in the ICU can lead to healthcare‐acquired infections (HCAIs).…”
Section: Introductionmentioning
confidence: 99%